2016
DOI: 10.1039/c6fd00072j
|View full text |Cite
|
Sign up to set email alerts
|

Protein detection using tunable pores: resistive pulses and current rectification

Abstract: We present the first comparison between assays that use resistive pulses or rectification ratios on a tunable pore platform. We compare their ability to quantify the cancer biomarker Vascular Endothelial Growth Factor (VEGF). The first assay measures the electrophoretic mobility of aptamer modified nanoparticles as they traverse the pore. By controlling the aptamer loading on the particle surface, and measuring the speed of each translocation event we are able to observe a change in velocity as low as 18 pM. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 60 publications
1
55
0
Order By: Relevance
“…Whilst some current rectification is observed here, it is likely to be a small contributing factor in the experiment and on a much smaller scale then seen in other TRPS systems. 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst some current rectification is observed here, it is likely to be a small contributing factor in the experiment and on a much smaller scale then seen in other TRPS systems. 40 …”
Section: Resultsmentioning
confidence: 99%
“…38,39 Conical nanopores, as used within TRPS, exhibit ionic rectification properties. [40][41][42][43] The charge on the pore wall creates areas of ion accumulation and depletion within the pore depending on the applied polarity. 42,[44][45][46] This leads to the current being higher at one voltage compared to the voltage of opposite polarity, often expressed as the rectification ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Only in recent years, nanopore technology has been extended to protein sequencing as nanopores could sequence full‐length proteins with high temporal and spatial resolution while traditional sequencing methods such as mass spectrometry and Edman degradation only rely on digestion of proteins into short peptides. Many experiments have shown that protein molecules can be electrophoretically driven through nanopores . Some experiments showed that proteins can be unfolded using nanopores by adjusting pH values of the solution, adding denaturing agents into the solution, increasing the applied bias voltage, elevating system temperature, using tiny nanopores smaller than the protein or by a molecular motor .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 This is measured through a change in translocation velocity and can provide quantitative information. [26][27][28] However RPS signals can be affected by the experimental setup. Studies have shown that ionic strength, off-axial translocation, the pore wall charge density and applied potential can affect the pulse size and width.…”
Section: Introductionmentioning
confidence: 99%